scikit-hep/mplhep: v.0.2.17rc - Andrzej Novak; actions-user; Matthew Feickert; Henry Schreiner; Jonas Eschle; Matthieu Marinangeli; N!no; Andreas; Andreas Weiden; Lindsey Gray; Balaji V Sathia Narayanan; Chris Burr; et al. (Zenodo, 2021)
Try manual release